A Reliability-Based Approach For Highway Bridges Subjected To Progressive Deterioration - Maizuar; Herman Fithra; Said Jalalul Akbar; Hamzani; Lis Ayu Widari; Zulfahmi (Faculty of Engineering, Malikussaleh University, 2018)
Progressive deterioration (e.g., corrosion) of the ageing bridge infrastructure is the main cause of structural deterioration and early failure of bridge especially in the marine environment. This paper presents a reliability-based approach for predicting the residual life of a bridge subjected to progressive deterioration. Specially, this study mainly focuses on developing a numerical approach for assessing the time-dependent probability of failure of a bridges. The results ofstudy show that the increase of progressive deterioration rates has a great impact on the decrease of bridge residual life. Further, the proposed realibility-based approach demonstrates the potential use for assessing probability of failure as well as predicting the residual life of bridges.